(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2014)
The methanation of carbon dioxide under atmospheric pressure over a Co-Ni/Al2O3 catalyst containing 5 wt% of metals prepared by the impregnation method was studied. Temperature of 95% conversion CO2 for all examined catalysts falls into range 320–450°C at conditions of SV 100 ml/min, 0.1 MPa pressure, and composition of feeding gas mixture CO2 – 2%, H2 – 55%, He – 43%. Methane selectivity was sufficiently high – up to 98%.